1958
DOI: 10.1042/bj0690596
|View full text |Cite
|
Sign up to set email alerts
|

The isolation of 3β-hydroxy-Δ5-steroids from the urine of normal men

Abstract: Dehydroepiandrosterone (3fl-hydroxyandrost-5-en-17-one) was the first steroid containing the 5-en-3flol group to be isolated from urine (Butenandt & Dannenbaum, 1934). During the succeeding twenty-two years only one other steroid of this type, namely androst-5-ene-3,B: 16x: 17fl-triol (Mar-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1959
1959
2011
2011

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The procedures used in the extraction of the urine and purification of the extract have already been described in detail (Fotherby, 1958). Briefly they consisted in boiling urine without adjustment of the pH, a procedure which appears to be specific for the hydrolysis of the 3,B-sulphates of 3,Bhydroxy-A5-steroids and separation and isolation of the 3#-hydroxy-A5-steroids present in the extract by countercurrent distribution and chromatography.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedures used in the extraction of the urine and purification of the extract have already been described in detail (Fotherby, 1958). Briefly they consisted in boiling urine without adjustment of the pH, a procedure which appears to be specific for the hydrolysis of the 3,B-sulphates of 3,Bhydroxy-A5-steroids and separation and isolation of the 3#-hydroxy-A5-steroids present in the extract by countercurrent distribution and chromatography.…”
Section: Resultsmentioning
confidence: 99%
“…The melting point indicated that this compound might bepregn-5-ene-3/:l16ac:20a.triol, and this was proved 14 to be so by comparing the acetate of the isolated material with authentic 3B: 16oc:20Oc-triacetoxypregn-5-ene. EXPERIMENTAL Details of the extraction of the urine, purification of the urine extract and the methods used have been published (Fotherby, 1958). lsolation of pregn-5-ene-3/3:16=:20o-triol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More general methods of detection were used for both steroid sulfates and free steroids in the present study and, as a consequence, our findings suggest that androstenediol sulfate is the major component of the sulfate fraction. No specific attempts were made to isolate either andrsstenediol disulfate or testosterone sulfate, but it was concluded from chromatographic evidence after hydrolysis (13) and solvolysis (14) that no more than trace amounts, if any, could have been present.…”
Section: Fig 3 Column Partition Chromatography On Celite As Ammonimentioning
confidence: 99%
“…It is produced in the adrenal glands. DHEA was the first steroid of its type to be isolated from the urine of a normal man, and identified as the most abundant steroid in human body 4 . DHEA and its metabolites have been found to strengthen the immune system in animals [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%